Effect of resilience training on stress, hope and psychological toughness of mothers living with mentally and physically disabled children - Pegah Sharifian; Zeinab kuchaki; Mahnaz shoghi (BMC, 2024)
Abstract Introduction Welfare and rehabilitation centers prioritize the welfare of children over the mental and physical well-being of mothers. The present study aimed to determine the impact of resilience training on stress, hope, and psychological toughness of mothers living with mentally and physically disabled children. Materials and methods This intervention study was conducted in the Hamadan (Iran) Welfare and Rehabilitation Center in 2023. To this end, 70 parents of children with mental and physical disabilities were randomly selected and then randomly assigned to two control and intervention groups. In the intervention group, 9 resilience training sessions were conducted, each lasting 60 min. These meetings were held weekly at the welfare and rehabilitation center. The resilience training included three components: (1) exploring the concept of resilience within families and the attributes of individuals with high resilience, (2) examining internal and external factors that influence resilience, and (3) studying the strategies for enhancing family resilience. No intervention was performed in the control group. Data collection was done using parental stress, hope, and psychological toughness questionnaire. The mothers of both groups completed the above questionnaires both before and one month after the intervention. Data analysis was performed using chi-square (χ2), Kruskal-Wallis, and t-test with SPSS software (version 23) at a significance level of 0.05. Results Before the intervention, there was no statistically significant difference in parental stress between the two groups (p = 0.370). However, after the intervention, the difference between the two groups became statistically significant (p = 0.001). Similarly, there was no significant difference in parents' hope before the intervention (p = 0.452), but a significant difference was observed after the intervention (p = 0.001). Besides, parental psychological toughness was not significant before the intervention (p = 0.179) but became significant after the intervention (p = 0.000). Conclusion Based on the results, resilience training reduced parental stress and increased hope and resilience in mothers of the test group. Therefore, resilience training is recommended to lower parental stress and increase the hope and psychological toughness of mothers of mentally and physically disabled children.